EPISTIMOLOGI ILMU PERSPEKTIF AL-QUR’AN "Studi Analisis Pada Buku Falsafah Al-Ma'rifah Fil Al-Qur'an Al-Karim Karya Abdul Adim" - Afifullah . (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2021)
The background of writing this article is that there are often differences of opinion about the relationship between the Qur'an and science. Some argue that the Qur'an is the source of everything, including science. Meanwhile, in other places, there are also those who argue that although the Qur'an is complete and perfect in its contents, it is not the source of everything. To gain knowledge, it is not enough just to read the Qur'an, but it must be accompanied by thought and research. Because the contents of the Qur'an cannot be said to be scientific knowledge. Due to frequent differences of opinion regarding the relationship between the Qur'an and science, the author feels the need to elaborate more deeply on Abdul Adim's thoughts on the relationship between the Qur'an and science in his book Philosophy al-Ma'rifah fi al-Qur'an. al-Karim. In this article, we find practical ways to find the correct knowledge according to the Qur'an in Abdul Adim's view. According to him, there are two methods in the epistemology of science, namely the method of hearing and the method of using reason. Each of the two methods has its own procedures.